Dietary citrate and plasma ionized calcium: Implications for platelet donors. Issue 3 (12th August 2017) - Haynes, Stefanie; Hickson, Elda; Linden, Jeanne; St. Pierre, Patricia; Ducharme, Paula; Sulmasy, Paula; Welch, Linda; Zhao, Yong; Greene, Mindy; Vauthrin, Michelle; Weinstein, Robert
Abstract: Background: Platelet donors receive 40 mmol or more of IV citrate anion during donation. When plasma ionized calcium ([Ca 2+ ]) falls by ∼20%, half of the donors report symptoms of hypocalcemic toxicity. Citrus juices contain clinically relevant amounts of citrate anion. We asked whether citrus juice can lower [Ca 2+ ] thus potentially contributing to hypocalcemic toxicity. Method: Six volunteers were given 20.4 mmol of citrate anion as grapefruit juice or orange juice. Capillary blood obtained by fingerstick was analyzed for [Ca 2+ ] using an iSTAT point‐of‐care blood analyzer. [Ca 2+ ] was measured at baseline and then 30, 60, 120, and 180 minutes after drinking juice. Subjects were tested with the alternative juice on a subsequent day. The outcome measure was the percent change in plasma [Ca 2+ ] from baseline. Results: [Ca 2+ ] fell −2.2% to −11.5% in four of six subjects 30 minutes after drinking grapefruit juice. The effect persisted up to 3 hours. [Ca 2+ ] fell −2.1% to −12.2% in four of six subjects 30‐60 minutes after drinking orange juice. The effect abated after 2 hours. We could not correlate gender or body surface area to these findings. Summary and Conclusions : Citrus juice may lower [Ca 2+ ] for 2‐3 hours. This could add to the effect of IV citrate infusion during platelet donation, thus worsening the expected fall in [Ca 2+ ]. This, in turn, would likely increase the rate and severity of hypocalcemic toxicity. It is prudent to advise platelet donors to avoid high citrate anion beverages, such as citrus juice, for at least 4 hours prior to donation.